2022
DOI: 10.1155/2022/4776243
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviates Acute Kidney Injury by Inhibiting NRF2/Slc7a11 Axis-Mediated Ferroptosis

Abstract: Acute kidney injury (AKI) is still a puzzling clinical problem; its pathophysiology is not completely understood. Up to now, an effective treatment for AKI is lacking. Ferroptosis is a novel form of regulated cell death characterized by the lethal accumulation of lipid hydroperoxides that are dependent on iron and reactive oxygen species and mitochondrial dysfunction. Recently, ferroptosis was shown to play a vital role in AKI such as ischemia-reperfusion kidney injury and folic acid-induced AKI. Melatonin (MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Inducible Gpx4 knockout mice directly aggravate lipid-oxidation-induced acute kidney injury and associated death [33]. Melatonin treatment significantly alleviates ischemia reperfusion-induced ferroptosis and acute kidney injury [47]. Folic acid induces ferroptosis, not necroptosis, in acute kidney injury [27], which can be rescued by quercetin through inactivation of transcription factor 3 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Inducible Gpx4 knockout mice directly aggravate lipid-oxidation-induced acute kidney injury and associated death [33]. Melatonin treatment significantly alleviates ischemia reperfusion-induced ferroptosis and acute kidney injury [47]. Folic acid induces ferroptosis, not necroptosis, in acute kidney injury [27], which can be rescued by quercetin through inactivation of transcription factor 3 [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HIFs, NRF2, the master regulator of oxidative stress signaling, also plays an important role in hypoxia-induced ferroptosis. Many studies reported that NRF mediates the regulation of ferroptosis induced by hypoxia or H/R [ 124 , 125 , 128 , 138 ], while another group of studies reported that targeting NRF2 could inhibit hypoxia-or H/R-induced ferroptosis [ 149 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dimethyl fumarate, a therapeutic agent for relapsing-remitting multiple sclerosis, inhibits H/R-induced ferroptosis in alpha mouse liver cells and a mouse liver IRI model by activating NRF2 pathway [ 163 ]. Melatonin, an antioxidant that regulates the sleep-wake cycle, was reported to inhibit RSL3-, erastin-, or H/R-induced ferroptosis through modulating NRF2, AKT, and GPX4, in hypoxic-ischemic brain damage, as well as through upregulating NRF2 and downregulating SLC7A11 in mouse tubular epithelial cells and a mouse acute kidney injury (AKI) model [ 164 , 165 ]. Moreover, gastrodin, one of the main functional substances of functional food raw material Gastrodia elata BI , inhibited hypoxia- or erastin-induced ferroptosis in hippocampal neurons by activating NRF2 and GPX4, as well as inhibiting KEAP1 and COX-2 [ 166 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%
“…Treatment with the GPX4 inhibitor RSL3 eliminates the protective effect of irisin ( Zhang et al, 2021b ). Melatonin and entacapone were confirmed to upregulate the nuclear translocation of Nrf2, resulting in increased expression of the downstream SLC7A11 and significant suppression of oxidative stress and ferroptosis ( Yang et al, 2022b ; Huang et al, 2022 ). Recent research revealed that dexmedetomidine could attenuate ferroptosis-mediated IRI-induced AKI by inhibiting ACSL4 ( Tao et al, 2022 ), and ACSL4 knockout also significantly alleviated this injury ( Wang et al, 2022b ).…”
Section: Ferroptosis In Different Types Of Acute Kidney Injurymentioning
confidence: 94%